Universal competences for sustainable development: defining boundaries and concepts - Karatkevich, Anna V.; Luchina, Viktoriya N. (Journal of the Belarusian State University. Ecology, 2019)
The crisis of the world technogenic civilization requires an adequate response in the form of the adoption of new philosophical and educational paradigms. Changes are needed in the global education system to meet the new and diverse needs of humanity. The reform of the educational system in the Republic of Belarus, as well as throughout the world, is associated with the use of a competency-based approach. Competence-based approach with its practical orientation and focus on the final result, is able to form a personality capable of conflict-free coexistence with the surrounding natural and social environment. Understanding the competencies as knowledge, skills and experience necessary to solve theoretical and practical problems, we attach great importance to the definition of the boundaries and content of competences, which are commonly called universal, or key. The formed universal competences are the qualities most relevant to the goals of sustainable development, since they contribute in the difficult problem situation to predict its development, and in the legal field to form a strategy for getting out of it into a sustainable future.